2006
DOI: 10.1002/ijc.22408
|View full text |Cite
|
Sign up to set email alerts
|

5α‐Reductase type 2 gene variant associations with prostate cancer risk, circulating hormone levels and androgenetic alopecia

Abstract: Controversy exists over the significance of associations between the SRD5A2 (5a-reductase type 2) polymorphisms, A49T and V89L, and risk of prostate cancer. These potentially functional polymorphisms may alter life-long exposure to androgens with subsequent effects on male health and aging. The aim of this study was to examine the association of these variants with prostate cancer risk, plasma hormone levels and androgenetic alopecia. Subjects include 827 cases and 736 controls from an Australian population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 27 publications
(51 reference statements)
1
27
0
2
Order By: Relevance
“…Another recent case-control study reported similar results, with combined frontal and vertex androgenetic alopecia at age 40 years associated with a reduction in odds of prostate cancer of 39% (16). It has been observed that carriers of a rare allele in the A49T polymorphism of the 5a-reductase type II gene are at greater risk of prostate cancer and a reduced risk of androgenetic alopecia (25). While this is consistent with an inverse association between androgenetic alopecia and prostate cancer risk, the evidence linking the polymorphism to prostate cancer risk is very weak.…”
Section: Discussionmentioning
confidence: 67%
“…Another recent case-control study reported similar results, with combined frontal and vertex androgenetic alopecia at age 40 years associated with a reduction in odds of prostate cancer of 39% (16). It has been observed that carriers of a rare allele in the A49T polymorphism of the 5a-reductase type II gene are at greater risk of prostate cancer and a reduced risk of androgenetic alopecia (25). While this is consistent with an inverse association between androgenetic alopecia and prostate cancer risk, the evidence linking the polymorphism to prostate cancer risk is very weak.…”
Section: Discussionmentioning
confidence: 67%
“…It has been reported that males with the VL and LL genotypes in comparison with those with the VV genotype exhibited a lower serum level of 3a-diolG (22). Conversely, Hayes et al (40) found no evidence of association between the SRD5A2 V89L polymorphism and testosterone, androstenedione, sex hormone-binding globulin or circulating levels of 3a-diolG and the risk of prostate cancer. The results of the study by Hayes et al (40) are concurrent with the results of the European Prospective Investigation into Cancer and Nutrition study performed in 2001 (41), which revealed that SRD5A2 V89L was associated with changes in the serum androgen levels, while another SRD5A2 A49T polymorphism caused a 24% reduction of circulating levels of 3a-diolG in carriers of the GA genotype compared with the GG genotype, leading to a 60% higher risk of developing prostate cancer (24,40).…”
Section: Discussionmentioning
confidence: 97%
“…Although certain studies have shown an association with prostate disease, the results are conflicting (25)(26)(27). As yet, there are no conclusions on whether V89L mutation is associated with the risk of prostate cancer (15,28), and there is no conclusive evidence of V89L polymorphism affecting serum …”
Section: Discussionmentioning
confidence: 99%
“…The most common variation is a valine to leucine substitution at codon 89 (V89L, rs523349), which has been associated with prostate cancer. Due to this variation, there is an approximately 30% reduced activity of SRD5A2 in Asian men (13), which is not found in European populations (14)(15). The other missense polymorphism is at codon 49, substituting an alanine with a threonine at codon 49 (A49T).…”
Section: Introductionmentioning
confidence: 99%